Thinking the Future Potential of Artificial Intelligence in Law Enforcement - Putri, Feby Milenia Yahya Krisna; Hakim, Hary Abdul; Praja, Chrisna Bagus Edhita; Espares, Gerald (Faculty of Law Hang Tuah University, 2024)
The use of Artificial Intelligence (AI) indicates the beginning of a new era in the development of digital technology. In general, AI's capabilities are considered to be able to solve problems which have been experienced by professionals, including AI robots which have also been widely used in law enforcement processes. However, the development of AI in law enforcement is certainly not without obstacles in which it is marked by the existence of a legal vacuum which forms the basis for the legality of AI use and a lack of literacy among law enforcers regarding the use of AI. In addition, law enforcement officials in Indonesia are still less aware of the benefits of using AI in order to support their profession. The aim of this study is to analyze the urgency of the implementation of AI for law enforcement in providing legal services and law enforcement processes. The research method used was a normative legal method with a statutory approach and a conceptual approach. Moreover, the analysis was conducted qualitatively and presented descriptively. The result shows that Artificial Intelligence (AI) is very important in helping develop services and law enforcement in which law enforcers in Indonesia so far still rely on manual or conventional methods in conducting their duties. Furthermore, AI can provide benefits in terms of time efficiency and accuracy in assessing cases which are urgently needed by law enforcement. Meanwhile, in terms of law enforcement's perception of the use of AI, they position AI as an assistant which cannot completely replace the law enforcement profession since AI does not have the human characteristics which law enforcement officers should have.